Frequent loss of the expression of multiple subunits of the SWI/SNF complex in large cell carcinoma and pleomorphic carcinoma of the lung. (8th September 2015) - Yoshimoto, Taichiro; Matsubara, Daisuke; Nakano, Tomoyuki; Tamura, Tomoko; Endo, Shunsuke; Sugiyama, Yukihiko; Niki, Toshiro
<x xml:space="preserve">Abstract</x> The switch/sucrose non‐fermenting (SWI/SNF) complex has recently emerged as a novel tumor suppressor in various human cancers. In the present study, we analyzed the expression of multiple SWI/SNF subunits in primary non‐small cell lung cancer (NSCLC). A total of 133 NSCLC, consisting of 25 squamous cell carcinomas (SCC), 70 adenocarcinomas (AD), 16 large cell carcinomas (LC), and 22 pleomorphic carcinomas (PL), were immunohistochemically examined for the expression of BRG1, BRM, BAF47, ARID1A, and ARID1B. The frequency at which reductions in the expression of BRG1 were observed was significantly higher in the LC‐PL group (13/38, 34.2%) than in the SCC‐AD group (7/95, 7.4%). Similarly, the frequency at which reductions in the expression of BRM were observed was significantly higher in the LC‐PL group (17/38, 44.7%) than in the SCC‐AD group (14/95, 14.7%). The loss of the expression of ARID1A, ARID1B, and BAF47 was observed only in a fraction of NSCLC cases. Furthermore, the frequency at which the concurrent loss of multiple subunits of the SWI/SNF complex was observed was significantly higher in the LC‐PL group (10/38, 26.3%) than in the SCC‐AD group (8/95, 8.4%). Collectively, these results indicate that the loss of the SWI/SNF complex was related to dedifferentiation in NSCLC.